2003
DOI: 10.1136/bmj.327.7406.84
|View full text |Cite
|
Sign up to set email alerts
|

Virtual outreach: economic evaluation of joint teleconsultations for patients referred by their general practitioner for a specialist opinion

Abstract: Objectives To test the hypotheses that, compared with conventional outpatient consultations, joint teleconsultation (virtual outreach) would incur no increased costs to the NHS, reduce costs to patients, and reduce absences from work by patients and their carers. Design Cost consequences study alongside randomised controlled trial. Setting Two hospitals in London and Shrewsbury and 29 general practices in inner London and Wales. Participants 3170 patients identified; 2094 eligible for inclusion and willing to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 22 publications
0
81
1
Order By: Relevance
“…The district clinicians, when deciding on the methods of referral for their patients, may have been influenced by the relatively short distances of 35 to 65 miles between their hospitals and London, even though emergency teleconsultations were easily arranged, particularly on weekdays. Our equivocal 6-month cost results differ from those of a randomized controlled trial of a telemedicine (virtual outreach) service for routine outpatient consultations in two NHS hospitals, in which the virtual outreach 6-month mean cost was significantly greater than the standard outpatient clinic cost (15). The virtual outreach system linked primary care physicians with consultants in eight specialties by means of personal computers and ISDN-2 lines (15;34).…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…The district clinicians, when deciding on the methods of referral for their patients, may have been influenced by the relatively short distances of 35 to 65 miles between their hospitals and London, even though emergency teleconsultations were easily arranged, particularly on weekdays. Our equivocal 6-month cost results differ from those of a randomized controlled trial of a telemedicine (virtual outreach) service for routine outpatient consultations in two NHS hospitals, in which the virtual outreach 6-month mean cost was significantly greater than the standard outpatient clinic cost (15). The virtual outreach system linked primary care physicians with consultants in eight specialties by means of personal computers and ISDN-2 lines (15;34).…”
Section: Discussioncontrasting
confidence: 78%
“…An annual equivalent cost for the telemedicine items in each hospital, including installation of the ISDN-6 lines and 17.5 percent value added tax (VAT), was calculated, with an expected lifetime for the equipment of 5 years (15), and an annual discount rate of 3.5 percent (14). Telephone bills provided details of ISDN-6 line rental, call charges, and VAT.…”
Section: Telemedicine Servicementioning
confidence: 99%
“…The relative efficiency of different options would depend on the implicit or explicit values attached by decision makers to the different elements of cost and outcome. Various options are compared in a easy to follow format which is displayed as tables [6].…”
Section: The Process Of Making Final Recommendationsmentioning
confidence: 99%
“…Teleorthopaedics involve the delivery of specialist services across a distance, usually between an orthopaedic surgeon and a patient [12]. It has been reported that teleorthopaedics in an outpatient setting is safe and without serious adverse events [13], that it has increased patient satisfaction [14,15] reduced travels and saved time for the patients [16,17] and reduced costs [18]. Teleorthopaedics can also improve the effectiveness of rehabilitation after orthopaedic surgery [4].…”
Section: Introductionmentioning
confidence: 99%